1993
DOI: 10.1093/tropej/39.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Children with  -Thalassemia Major in North Jordan

Abstract: Basal thyroid function was assessed by serum thyroxine, tri-iodothyronine and thyroid-stimulating hormone levels in 90 patients 2-10 years old with beta-thalassaemia major. Based on measured serum ferritin levels, patients were classified into two groups: group (I) which included 63 patients with ferritin concentrations ranging from 300 to 7000 ng/ml (mild iron overload) and group (II) which included 27 patients with ferritin concentrations higher than 7000 ng/ml (severe iron overload). The results of thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
2
2
1
2
Order By: Relevance
“…Probably for this reason iron overload had no major contribution in thyroid hypo function in the present study. This observation did not support the findings of Al-Hader et al 4 who found that thyroid hypofunction is common in thalassaemic patients with iron overload. Agarwal et al 17 and Masala and his coworker 21 did not observe any significant correlation between iron overload and thyroid status.…”
Section: Methodscontrasting
confidence: 96%
See 1 more Smart Citation
“…Probably for this reason iron overload had no major contribution in thyroid hypo function in the present study. This observation did not support the findings of Al-Hader et al 4 who found that thyroid hypofunction is common in thalassaemic patients with iron overload. Agarwal et al 17 and Masala and his coworker 21 did not observe any significant correlation between iron overload and thyroid status.…”
Section: Methodscontrasting
confidence: 96%
“…Transfusion related iron overload is the primary therapeutic complication in thalassaemia 4 . Beside heart and liver, endocrine organs of the body bear the brunt of iron mediated insult 5 .…”
Section: Table 1: Demographic Profile Of Study Populationmentioning
confidence: 99%
“…We found that thyroid dysfunction did not correlate with serum ferritin level. Similar observations have been made by others 12,13,14 .…”
supporting
confidence: 92%
“…MB Agarwal et al reported subclinical hypothyroidism in 6.9% of thalassemic children but none of the patients in their study had overt clinical evidence of hypothyroidism [16]. In accordance with the observations made by other researchers, it is unlikely that thyroid dysfunction correlates with serum ferritin level [17][18][19].…”
Section: Discussionsupporting
confidence: 70%